1978
DOI: 10.1073/pnas.75.4.2044
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of estradiol and progesterone on oxytocin receptors in rabbit uterus

Abstract: Estradiol-17# administration to young (10-to 12-week-old) rabbits to produce the "estrogen-dominated" uterus increased the uterine contractile response to both oxjtocin and methacholine in vitro. In "progesterone-dominatel" uteri, obtained from rabbits that received progesterone for 4 days after estrogen pretreatment, the contractile response to oxytocin in vitro was selectively abolished; the response to methacholine was unaffected. Parallel changes were observed in the concentration (but not affinity) of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 18 publications
4
43
0
2
Order By: Relevance
“…The major rise in oxytocin receptor at oestrus appears to be closely linked to declining levels of progesterone and the induction of the receptor by oestrogen can be blocked by progesterone both in vivo (Nissenson, Flouret & Hechter, 1978) and in vitro (Soloff et al, 1983); there is therefore evidence that such a mechanism might operate. As reviewed above it appears most likely that oxytocin infusion delays luteolysis through an inhibitory action on PGF-2rx secretion; it is possible, therefore, that oxytocin affects prostaglandin synthesis, perhaps by reducing the availability of substrate to the synthetase, as a result of interacting with the relatively low levels of oxytocin receptor in the uterus on Day 13 of the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The major rise in oxytocin receptor at oestrus appears to be closely linked to declining levels of progesterone and the induction of the receptor by oestrogen can be blocked by progesterone both in vivo (Nissenson, Flouret & Hechter, 1978) and in vitro (Soloff et al, 1983); there is therefore evidence that such a mechanism might operate. As reviewed above it appears most likely that oxytocin infusion delays luteolysis through an inhibitory action on PGF-2rx secretion; it is possible, therefore, that oxytocin affects prostaglandin synthesis, perhaps by reducing the availability of substrate to the synthetase, as a result of interacting with the relatively low levels of oxytocin receptor in the uterus on Day 13 of the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on various species have shown that E 2 increases the expression of genes in myometrial cells encoding gap junction proteins that form low-resistance connections between myometrial cells to promote synchronized contractions , Kilarski et al 1996, receptors for uterotonic hormones such as oxytocin and prostaglandin F 2a (PGF 2a ; Pinto et al 1966, 1967, Nissenson et al 1978, and enzymes such as PG-endoperoxide synthase-2 (PTGS2), the main inducible rate-limiting enzyme for PG synthesis (Mesiano et al 2002). Although it is generally accepted that these actions are mediated by estrogen receptors (ERs), the specific ERs and associated signaling pathways are not well characterized in the pregnant human myometrium.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is an outcome of uterine oestrogen dominance which is made possible by a sharp rise in oestrogen receptor concentration during the preceding 24 h. Since progesterone restrains oestrogenreceptor synthesis (Hsueh et al, 1976;Nissenson et al, 1978;Okulicz et al, 1981), attainment of the proper oestrogen/progesterone ratio in the plasma is crucial to the chain of events which will culminate in labour. Doubling of the progesterone concentration and thus halving of the oestrogen/progesterone ratio (as occurred in our zinc-deficient rats) would be, according to the results of Bercu et al (1980), sufficient to impede oestrogen-receptor synthesis.…”
Section: Resultsmentioning
confidence: 99%